Transmission rate and reproductive number of the H5N1 highly pathogenic avian influenza virus during the December 2005-July 2008 epidemic in Nigeria - Bett, Bernard K.; Henning, J.; Abdu, P.; Okike, Iheanacho; Poole, Elizabeth J.; Young, J.; Randolph, Thomas F.; Perry, Brian D. (Hindawi Limited, 2014)
We quantified the between-village transmission rate, β (the rate of transmission of H5N1 HPAI virus per effective contact), and the reproductive number, Re (the average number of outbreaks caused by one infectious village during its entire infectious period), of H5N1 highly pathogenic avian influenza (HPAI) virus in Nigeria using outbreak data collected between December 2005 and July 2008. We classified the outbreaks into two phases to assess the effectiveness of the control measures implemented. Phase 1 (December 2005–October 2006) represents the period when the Federal Government of Nigeria managed the HPAI surveillance and response measures, while Phase 2 (November 2006–July 2008) represents the time during which the Nigeria Avian Influenza Control and Human Pandemic Preparedness project (NAICP), funded by a World Bank credit of US$ 50 million, had taken over the management of most of the interventions. We used a total of 204 outbreaks from 176 villages that occurred in 78 local government areas of 25 states. The compartmental susceptible-infectious model was used as the analytical tool. Means and 95% percentile confidence intervals were obtained using bootstrapping techniques. The overall mean β (assuming a duration of infectiousness, T, of 12 days) was 0.07/day (95% percentile confidence interval: 0.06–0.09). The first and second phases of the epidemic had comparable β estimates of 0.06/day (0.04–0.09) and 0.08/day (0.06–0.10), respectively. The Re of the virus associated with these β and T estimates was 0.9 (0.7–1.1); the first and second phases of the epidemic had Re of 0.84 (0.5–1.2) and 0.9 (0.6–1.2), respectively. We conclude that the intervention measures implemented in the second phase of the epidemic had comparable effects to those implemented during the first phase and that the Re of the epidemic was low, indicating that the Nigeria H5N1 HPAI epidemic was unstable.